A computational and experimental method for determining the initial conditions of motion of foreign objects interacting with a surface vortex - E. V. Neskoromnyy; S. A. Borozdin; A. I. Yevdokimov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
An experimental method has been developed that makes it possible to obtain the kinematic parameters of a particle moving in an air stream, while colliding with the surface of an airfield. The experimental setup and methodology of the experiment are described, and the main results are presented in the form of the density and distribution function of the angles of incidence and reflection for the case of collision of granite particles with a fragment of an airfield slab. The obtained statistical characteristics are the initial data for modeling the process of ingress of foreign objects into the entrance to the power plant.